2011
DOI: 10.15669/pnst.2.598
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of UO2 by Molecular Dynamics Simulation

Abstract: Molecular dynamics (MD) simulation was performed to investigate thermal expansion, specific heat and thermal conductivity of UO 2 . For thermal expansion, experimental measurements were made and compared with MD simulation results. These thermal expansion values and other reported data were in good agreement with the MD thermal expansion value. Effects of Schottky defects on thermal properties were evaluated. For thermal expansion, the effect was negligible. For specific heat, the constant volume term of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…MD simulations for pure UO 2 were carried out using the potential from Busker et al [24], at temperatures ranging from 200 K to 1500 K. These MD results consistently overpredict the thermal conductivity of UO 2 , as has been previously observed in the literature [25,26]. This is primarily due to resonant scattering of phonons by spins in the paramagnetic phase of UO 2 [23,27], which is not captured by the MD simulations.…”
Section: Modeling the Effect Of Dispersed Fission Gas Atomsmentioning
confidence: 70%
“…MD simulations for pure UO 2 were carried out using the potential from Busker et al [24], at temperatures ranging from 200 K to 1500 K. These MD results consistently overpredict the thermal conductivity of UO 2 , as has been previously observed in the literature [25,26]. This is primarily due to resonant scattering of phonons by spins in the paramagnetic phase of UO 2 [23,27], which is not captured by the MD simulations.…”
Section: Modeling the Effect Of Dispersed Fission Gas Atomsmentioning
confidence: 70%
“…4 shows the Pu content dependence of thermal expansion for (U,Pu)O 2.00 . The data of UO 2 and PuO 2 were measured with the same apparatus as in previous reports [12,18]. In the high temperature range above 1500 K, U 0.7 Pu 0.3 O 2 had the highest thermal expansion.…”
Section: Resultsmentioning
confidence: 96%
“…(5), and coefficients a 0 , a 1 , a 2 and a 3 were obtained. Uchida et al [12,18] and Kato et al [19] reported thermal expansion and derived the equations for UO 2 and PuO 2 . Their data were reassessed by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Konduktivitas panas suatu material dipengaruhi oleh struktur kristal dan kesempurnaannya, dinamika kisi, kestabilan struktur, porositas dan ukuran butir [10,[14][15][16][17][18]. Hasil perhitungan dispersi phonon dengan simulasi molekular dinamis pada struktur elektronik UO 2 , mengungkapkan bahwa konduktivitas panas UO 2 yang rendah merupakan efek dari ketidakharmonisan struktur yang besar pada optical modes dari phonon sebagai pembawa panas [14].…”
Section: Pendahuluanunclassified